2011
DOI: 10.1007/s10875-011-9518-6
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Interferon-α/β Receptors in Chronic Hepatitis B Patients

Abstract: Background The present study determined type I interferon (IFN) receptor (interferon-α/β receptor (IFNAR)) and its predicable role in interferon-α2b treatment in chronic hepatitis B (CHB) patients. Methods Expression of IFN-α/βR-1 and IFN-α/βR-2 in peripheral blood mononuclear cells and in liver tissue was measured by flow cytometry, immunofluorescence, immunohistochemistry and RT-PCR. Results IFN-α/βR-1 and IFN-α/βR-2 in monocytes and lymphocytes increased in CHB patients. Expression of IFNAR-1 and IFNAR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Our subgroup analyses further observed that during PEG-IFN- α -2a treatment, the expression of NKp46 and IFNAR2 on NK cells in nonresponse group had no significant differences compared with baseline, but in the response group, the expression of NKp46 and IFNAR2 on NK cells significantly enhanced, which suggested that the activation of NKp46 and IFNAR2 was related to the therapeutic effect. These results were consistent with previous findings [ 18 , 31 , 32 ] and further support the direction of using the aforementioned parameters as the early indicator to predict treatment response. This study suggested that NK cell function was not associated with changes in HBV DNA loads and HBeAg levels before treatment and during early treatment, but the HBsAg decrease was positively associated with NKp46 bright NK frequency before treatment and at treatment week 12.…”
Section: Discussionsupporting
confidence: 92%
“…Our subgroup analyses further observed that during PEG-IFN- α -2a treatment, the expression of NKp46 and IFNAR2 on NK cells in nonresponse group had no significant differences compared with baseline, but in the response group, the expression of NKp46 and IFNAR2 on NK cells significantly enhanced, which suggested that the activation of NKp46 and IFNAR2 was related to the therapeutic effect. These results were consistent with previous findings [ 18 , 31 , 32 ] and further support the direction of using the aforementioned parameters as the early indicator to predict treatment response. This study suggested that NK cell function was not associated with changes in HBV DNA loads and HBeAg levels before treatment and during early treatment, but the HBsAg decrease was positively associated with NKp46 bright NK frequency before treatment and at treatment week 12.…”
Section: Discussionsupporting
confidence: 92%
“…It was shown that a decrease in cell surface concentration of one or both of the receptor subunits reduces cell sensitivity and alters signaling (5,25,26,43,49). In addition, a clear correlation between the efficiency of interferon as an antiviral drug or a cancer drug and surface receptor concentration was suggested (7,12,27,49). Using stably transfected cells, it was shown that an increased number of receptors resulted in an overall elevated sensitivity for IFNs, accompanied by a de-* Corresponding author.…”
mentioning
confidence: 99%
“…Peripheral IFNAR The mechanisms are not clear and may related to oxidative stress and the disturbance of IFNAR function (37,52).…”
Section: Cytokines Chemokines and Non-coding Rnasmentioning
confidence: 99%
“…Studies showed that IFNAR1 and IFNAR2 in peripheral blood mononuclear cells and lymphocytes increased in CHB patients, but their level had a positive correlation with HBV-DNA in liver tissue ( 37 ). Several negative regulators mainly functioning to suppress IFNs expression or disturb the function or expression of IFNAR, thereby inhibit the JAK-STAT pathway and ISGs production ( Figure 1 ).…”
Section: Negative Regulators In Ifn Induction and Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation